MAiD in Canada: Ethical Considerations in Medical Assistance in Dying - Nielsen, William (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
Medical assistance in dying (MAiD) is unique among the arsenal of medical therapeutics though it does return us to a dilemma Hippocrates addressed 2400 years ago. It provides welcome relief for suffering patients and their families, but MAiD is not suicide – it is invited homicide. It is more like a death ritual than a therapeutic procedure. Unlike medical interventions, MAiD cures no diseases and true informed consent cannot be obtained. It separates the body from the soul and perceived doctors’ errors are punishable through criminal prosecution. If badly administered, it could undermine trust in the medical profession. The providers are also at risk for delayed remorse. As the inclusion criteria for MAiD become more relaxed, doctors who currently decide on candidates for MAiD should have access to established panels for guidance. The panels should include legal and ethical specialists.